Implementation Of Standard Operating Procedures In Increasing Work Productivity Workers Wangi Sedap Catering - Susi Marta Tambunan (Enrichment : Journal of Management, 2022)
Wangi Sedap Catering is one of the businesses engaged in food and beverage processing where this business still uses a manual system that requires professional employees in their field to avoid complaints from customers, therefore a good operational procedure system is needed to produce professional workers in manage the Wangi Sedap Catering in business, therefore standard operating procedures are very important in increasing employee productivity. The formulation of the problem in this research is Does the implementation of standard operating procedures have an effect on increasing work productivity for the Wangi Sedap Catering workforce at the Tourism Academy of Medan Hotel School? The research conducted at H. Bahrum Jamil street No. 48 Medan, North Sumatera The type of this research is descriptive qualitative research. The method of data collection was done through interviews, documentation and questionnaires. The number of samples in this study were 10 people. The hypothesis in this study is that it is estimated that standard operating procedures have an effect on increasing the work productivity of Wangi Sedap Catering workers at the Tourism Academy of Medan Hotel School. The results of the study: 1. Standard Operating Procedures influences to increasing employee productivity of Wangi Sedap Catering at the Tourism Academy f Medan Hotel School. 2. The most dominant indicator of The standard operating procedure to influences the work productivity of the workforce of Wangi Sedap Catering at the Tourism Academy of Medan Hotel School is the standardized procedure for Wangi Sedap Catering has been determined by the leadership as a product adhered to be implemented and becomes an instrument to protect the apparatus from lawsuits., 3. The most dominant indicator of work productivity is Quality, which is the result of work that can show the work quality of Wangi Sedap Catering's workforce.